INTERVENTION STUDY WITH SCHOOLCHILDREN USING THE CARD GAME "THE PYRAMID ENIGMA" ABOUT HEALTHY EATING - Vasconcelos, Celia Maria Ribeiro de; Vasconcelos, Eliane Maria Ribeiro de; Ramos, Vânia Pinheiro; Vasconcelos, Ana Lucia Ribeiro de; Raposo, Maria Cristina Falcão; Moura, Jeﬀerson Wildes da Silva; Oliveira, Raimundo Valmir de (Cogitare Enfermagem, 2022)
Objective: to evaluate the knowledge about healthy eating promoted by educational technology. Method: quasi-experimental (pre/posttest design) performance evaluation study. test design). Participated 204 students, aged between nine and 10 years, from three public schools of Recife-PE-Brazil, in September 2018. Knowledge gain was observed by the following process: decreasing from the Mean Score Observed after the intervention (PMO-2) to the Mean Score Observed before the intervention (PMO-1); dividing the number obtained by PMO-1 and then multiplying the result obtained by 100. Results: before the intervention 16/204 students (7.8%) scored ≥ 7. After the intervention 160/204 students (78.4%) achieved this score. The proportion of students who scored ≤ 5 went from 49/204 (24%) to 1/204 (0.5%). Four students maintained their initial score. The average knowledge gain after a single move was 38.5%. Conclusion: these results proved the effectiveness of the game, and its use promoted socialization among the students.